FORMULASI DAN UJI STABILITAS FISIK SEDIAAN TABLET EKSTRAK BUAH PARE (Momordica charantia L.) SECARA GRANULASI BASAH - Ira nur fadhilah; Dwi Saryanti (Smart Medical Journal, 2019)
Bitter melon fruit is one type of medicinal plant used by the community. Charantin is one of the efficacious compounds contained in bitter melon fruit and can be used to reduce glucose levels in the blood. Tablets have advantage that are easy to consume and exactly the size, so in this study bitter melon is made from tablet preparations. The purpose of this study was to determine the concentration of gelatin binder which can produce tablets of bitter fruit extract (Momordica charantia L.) with good physical quality, and to determine the effect of gelatin as a binder on the physical stability test of bitter melon extract tablets (Momordica charantia L.) making bitter melon extract tablets is by wet granulation method, because the active ingredient of bitter melon fruit is not resistant to warming above 600C. Formulation tablets of bitter melon extract (Momordica charantia L.) with gelatin binder at a concentration of 5%, 7.5%, 10% able to produce tablets that meet the requirements of tablet physical examination for 28 days. Gelatin binding concentration has an effect on the physical properties of tablets, the best concentration of gelatin binder is formula III with 10% gelatin concentration. The higher the concentration of the binding material, the higher the hardness, and fragility decreases.Keywords: Bitter Melon Extract (Momordica charantia L.), Gelatin binder, Wet Granulation.